Patterns of Otorhinolaryngological Manifestations of Covid-19: A Longitudinal Questionnaire-Based Prospective Study in a Tertiary Hospital in Saudi Arabia - Danah Alrusayyis; Hussain Aljubran; Askar Alshaibani; Salma Alsharhan; Abdulmalik AlSaied; Abdulaziz ALEnazi; Amal Alghamdi; Saad Alshahrani; Abdul Salam; Mohammed Al Bar (SAGE Publishing, 2022)
Objective: Many studied investigated the manifestations of COVID-19, yet few described the pattern and severity of otolaryngological symptoms. We aim to describe the picture of COVID-19-associated otorhinolaryngological manifestations and recovery to explore individualized treatment, onward referral, and complications prevention. Design: Prospective longitudinal questionnaire-based study. Setting: The online questionnaire was filled 3 times through a remote interview over a period of 1 month from June 2020 to July 2020. Participants: Patients with confirmed COVID-19 by RT-PCR who were clinically stable. Main Outcome Measures: Date of diagnosis, sociodemographic data, and the presence of predictive factors, such as nasal and paranasal disease, anosmia and dysgeusia. Validated tools were used, such as Sino-nasal Outcome Test (SNOT-22), smell test (medical academy screening tool), Voice Handicap Index (VHI), and Reflux Symptoms Index (RSI). Result: The questionnaire was sent to 363 patients and the response rate was 70.80% (n = 257). The mean age was 34.58 years (SD = 11.22) and the rate of male participants was 60.7%. The most common otorhinolaryngological symptoms at the time of enrollment was fever (48.6%), whilst the commonest severe symptom was cough (57%). After 1 month, only 11 participants had persistent severe symptoms, especially sleep and psychological symptoms (73%), and the majority were female (63.6%). All of them had at least 1 comorbidity. There was a significant difference between the mean age of participants with severe symptoms (mean = 27.45, SD = 8.39) and without severe symptoms (mean = 34.90, SD = 2.53, t (255) = 2.17, P  = .031). Conclusion: COVID-19 has a wide-ranged spectrum of presentations, with otorhinolaryngological symptoms being the commonest and most serious. Studying these symptoms is vital to advance management options.